Peranan Kualitas Pelayanan Pendidikan Terhadap Tingkat Kepuasan Mahasiswa Menggunakan Pendekatan Importance Performace Analysis (Studi Kasus Di Universitas Sangga Buana) - Heru Azhar Adlirachan; Inayati Nasrudin (Prodi Manajemen S1 dan D3 Keuangan & Perbankan, 2019)
This research purposed to identify and analyze how far the service quality to the level of customer’s satisfaction (Case Study in Sangga Buana University), By results of data processed on respondent preferences , it generally showed that each of variable of sevice quality has a suitability of expectation 61.20% (X1), 65.77% (X2), 65.82% (X3), 68.75% (X4), and 67.69% (X5) to customer’s satisfaction. In fact, evidently among the five dimension, only dimesion of tangible, reliability, emphaty and responsiveness was in quadrant A and B with percentace of customer”s statisfaction 48% and 34%, on the otherhand dimension of assurance was in quadrant C and D with percentace of customer”s statisfaction 4% and 12%. In addition, the F-test showed that service quality had a low significant impact on customer’s satisfaction with the level of significance of 0.1 or 10%. This matter can be seen from all of t-count variable which hasn’t exceed t-table. Based on the cartecius diagram, There are 24 indicators in quadrant A, 2 indicators in quadrant C, and 6 indicators in quadrant D need to be improved. Furthermore, there are 17 indicators in quadrant B as a good services.